Crack Failure Characteristics of Different Rocks Under the Action of Frost Heaving of Fissure Water - Zhang, Guangze; Chen, Guoqing; Xu, Zhengxuan; Yang, Yang; Lin, Zhiheng (Frontiers in Earth Science, 2020)
Freeze-thaw problems need to be solved urgently with the construction of projects in the alpine mountain areas. Freeze-thaw cycle tests with different cycles were carried out after water was filled in the crack. Combined with the theory of frost heaving mechanics and fracture mechanics, the failure modes and mechanical characteristics of crack growth are analyzed after the freeze-thaw cycle test. The research results showed the crack growth increase with the number of freezing-thawing cycles. Cracked rock failure types are divided into four types. The Poisson's ratio, elastic modulus of rock and water-ice medium, the equivalent volume expansion coefficient of water-ice medium determine the size of frost heaving force generated in fractured rock. The upper saturated crack of limestone and red sandstone produces pure mode-I fracture under the action of the freeze-thaw cycle. The cracks in the fractured rock mass will extend along the direction of this structural plane when there is a visible weak structural surface in the rock mass. The research results can provide a reference for the freezing and thawing splitting effect caused by rainwater infiltration in mountainous alpine areas.